2013
DOI: 10.1155/2013/705185
|View full text |Cite
|
Sign up to set email alerts
|

Development and Kinematic Verification of a Finite Element Model for the Lumbar Spine: Application to Disc Degeneration

Abstract: The knowledge of the lumbar spine biomechanics is essential for clinical applications. Due to the difficulties to experiment on living people and the irregular results published, simulation based on finite elements (FE) has been developed, making it possible to adequately reproduce the biomechanics of the lumbar spine. A 3D FE model of the complete lumbar spine (vertebrae, discs, and ligaments) has been developed. To verify the model, radiological images (X-rays) were taken over a group of 25 healthy, male ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 59 publications
(101 reference statements)
1
37
0
Order By: Relevance
“…The simulation results that were presented in this study showed an increase in angular displacement during flexion in the order L1/2 (2.6 • ) → L2/3 (3.6 • ) → L3/4 (4.4 • ) → L4/5 (4.6 • ). This caudocranial increase in angular IVD joint motion is in accordance with flexion-extension studies by Hayes et al (1989), Ibarz et al (2013), Pearcy and Portek (1984), White and Panjabi (1990): L1/2 (5 − 16 • ) → L2/3 (7.8 − 18 • ) → L3/4 (6 − 17 • ) → L4/5 (9 − 21 • ). Again, only relative changes could be presented (see Fig.…”
Section: Appendix 6: Muscle Parameterssupporting
confidence: 91%
See 4 more Smart Citations
“…The simulation results that were presented in this study showed an increase in angular displacement during flexion in the order L1/2 (2.6 • ) → L2/3 (3.6 • ) → L3/4 (4.4 • ) → L4/5 (4.6 • ). This caudocranial increase in angular IVD joint motion is in accordance with flexion-extension studies by Hayes et al (1989), Ibarz et al (2013), Pearcy and Portek (1984), White and Panjabi (1990): L1/2 (5 − 16 • ) → L2/3 (7.8 − 18 • ) → L3/4 (6 − 17 • ) → L4/5 (9 − 21 • ). Again, only relative changes could be presented (see Fig.…”
Section: Appendix 6: Muscle Parameterssupporting
confidence: 91%
“…some present increasing angular motion from cranial to caudal (Hayes et al 1989;Ibarz et al 2013;Pearcy and Portek 1984;White and Panjabi 1990) while others present the opposite (Lee et al 2002;Li et al 2009;Wong et al 2004Wong et al , 2006. The simulation results that were presented in this study showed an increase in angular displacement during flexion in the order L1/2 (2.6 • ) → L2/3 (3.6 • ) → L3/4 (4.4 • ) → L4/5 (4.6 • ).…”
Section: Appendix 6: Muscle Parametersmentioning
confidence: 49%
See 3 more Smart Citations